Eye‐Readable Detection and Oxidation of CO with a Platinum‐Based Catalyst and a Binuclear Rhodium Complex. (22nd July 2019) - Qu, Jiafu; Cao, Yueqiang; Duan, Xuezhi; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Chen, Dongyun; Lu, Jianmei
Abstract: Toxic gases that are colorless and odorless, such as CO, are a major environmental concern and require early detection to prevent serious toxicological effects. In this study, a unique system (Pt/HMSs‐BRC) was fabricated by combining a catalyst (Pt/hollow mesoporous silica spheres, Pt/HMSs) with a silica gel containing an adsorbed chromogenic probe (binuclear rhodium complex, BRC). The process is a simple method to prepare well‐dispersed and uniform Pt nanoparticles. The Pt/HMSs‐BRC materials demonstrated early CO detection and excellent catalytic performance for CO oxidation. The probe exhibited remarkable color modulation from gray‐violet to light‐yellow when exposed to CO concentration levels above 50 ppm, and the color of the chromogenic probe was fully recoverable. By a kinetics‐assisted discrimination method and DFT calculations, it was found that the corner Pt sites are the dominant active sites for CO oxidation. Abstract : Jetzt siehst du es, jetzt nicht mehr : Für den simultanen Nachweis und die katalytische Umwandlung von CO wurde eine chromogene Sonde an Kieselgel adsorbiert und mit einem Pt‐Katalysator auf mesoporösen Hohlkugeln (HMS) kombiniert (siehe Bild). Der Pt/HMS‐Katalysator wandelt 100 % des CO um, und die chromogene Sonde zeigt eine bemerkenswerte Farbänderung bei CO‐Konzentrationen über 50 ppm.